Relative Significance of Journals, Authors, and Articles Cited in Financial Research. - Alexander, John C; Mabry, Rodney H (Journal of Finance, 1994)
The authors evaluate journals based on their relative contributions to top-level finance research in a recent period. Journals are ranked according to the number of citations found in articles published in the Journal of Finance, Journal of Financial Economics, Journal of Financial and Quantitative Analysis, and Review of Financial Studies. The analysis controls for both the average number of articles and average number of words published annually in each cited journal. The authors identify the fifty most frequently cited journals during this period. They also list the fifty most frequently cited authors and articles and note topical trends in the research.